Psychological-creative Portraits Of The Tsisperkhantselebi Based On Two Novels By Nino Chkhikvishvili: ("I’m The Last Tsisperkhantseli” And “I Am Paolo”) - Urdulashvili, Lali (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2018)
Nino Chkhikvishvili’s works reflect in-depth knowledge and analysis of the life and work of the Tsisperekhantselebi, which is provided by the scientific and publicist literature of their modern and later times. In this regard, Nino Chkhikvishvili is a tireless researcher of the works of representatives of symbolic poetry. She studies each documentary by diligence and uses them in her novels with her writing mastery. Nino Chkhikvishvili’s book “The Last Tsisperkhantseli” is a biographical novel dedicated to Kolau Nadiradze. “The Proud Knight of the Blue Order,” that’s how the author mentions Collau at the end of the book. We should also note that the life of the last tsisperkhantseli vividly shows Paolo’s personality, together with Collau, his indispensable role and meaning in literary space of symbolic poets, even at the public presence of the epoch. Memories relate to prominent personalities of Georgian literature and culture who have said their words in various fields of art. Nino Chkhikvishvili highlights the history of the creation of the poem which rose the poet “on the shield”. This is “February 25, 1921”. Kolau fondly recalled the years spent in Kutaisi, a classical gymnasium where his beloved teacher, Meliton Chogovadze, taught Georgian. Kantseli himself was the witness of the amazing fact regarding Akaki’s jubilee when gymnasium students freed horses from the carriage and drove it by themselves to take the writer to the theatre. Nino Chkhikvishvili emphasizes that the term Funagoria is precisely the one that was coined by Colau Nadiradze in our literature and names many of them. Nino Chkhikvishvili’s second book, “I’m Paolo,” is dedicated to Paolo Iashvili. It seems like a logical continuation of the novel “The Last Tsisperkhantseli”. Nino Chkhikvishvili erected a monument with her novels to the Tsisperkhantseli Brotherhood.